An analysis of the Topeka Kansas downtown district to determine a process of rejuvenation - Munz-Pritchard, Christine Patricia (Kansas State University, 2011)
This report is a reconnaissance analysis of the Topeka, Kansas downtown district to determine a process of rejuvenation. Many office buildings are established in or near the downtown core, and bring an estimated 30,000 employees to the area; however, after 5:00 PM much of the work force leaves the downtown making it difficult for retail and entertainment businesses to stay open. The purpose of this study is to analyze the downtown district of Topeka in terms of its strengths and weaknesses, and determine the steps that must be taken before a process of rejuvenation can occur. To accomplish this, the study examines strategic data such as a workforce profile, location information, public facilities, historical and current demographics of the city, along with specific information on the downtown area such as past and present plans for renovation. This analysis also includes current plans in the downtown and how they might impact the future physical development of the central core of downtown Topeka such as the potential realignment of Interstate 70. The key to making any downtown project a success is to acknowledge the weaknesses and threats of the area and to recast them as potential opportunities and strengths for the area. This is why the study has a building survey and a S.W.O.T. (Strengths, Weaknesses, Opportunities, and Strengths) analysis.
Keywords: Rejuvenation; Topeka; SWOT; Downtown; Urban Planning (0999)